2015
DOI: 10.1016/j.schres.2015.09.022
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a ketogenic diet on auditory gating in DBA/2 mice: A proof-of-concept study

Abstract: Although the ketogenic diet has shown promise in a pilot study and case report in schizophrenia, its effects in animal models of hypothesized disease mechanisms is unknown. This study examined effects of treatment with the ketogenic diet on hippocampal P20/N40 gating in DBA/2 mice, a translational endophenotype that mirrors inhibitory deficits in P50 sensory gating in schizophrenia patients. As expected, the diet increased blood ketone levels. Animals with the highest ketone levels showed the lowest P20/N40 ga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 40 publications
0
7
0
Order By: Relevance
“…In schizophrenia, comorbidity with IBS [73], non-celiac gluten sensitivity [74], and the correlation between the amount of Lactobacillus and the severity of the symptomatology [75] also provide evidence of a possible connection to the MGB. Indeed, a reduction in the symptoms associated with the schizophrenia spectrum, such as delusions or disorganized behavior, has been associated with the use of a ketogenic diet [76], which could activate the auditory sensory gating deficit characterized in schizophrenia patients, as suggested in preclinical studies in DBA/2 mice [77].…”
Section: How Are Gut and Brain Diseases Related To Each Other?mentioning
confidence: 99%
“…In schizophrenia, comorbidity with IBS [73], non-celiac gluten sensitivity [74], and the correlation between the amount of Lactobacillus and the severity of the symptomatology [75] also provide evidence of a possible connection to the MGB. Indeed, a reduction in the symptoms associated with the schizophrenia spectrum, such as delusions or disorganized behavior, has been associated with the use of a ketogenic diet [76], which could activate the auditory sensory gating deficit characterized in schizophrenia patients, as suggested in preclinical studies in DBA/2 mice [77].…”
Section: How Are Gut and Brain Diseases Related To Each Other?mentioning
confidence: 99%
“…Additionally, it inhibits histone deacetylases and promotes metabolic regulation [35]. The KD improves neuronal function by lowering glutamate toxicity, increasing GABA inhibitory tone, and decreasing reactive oxygen species (ROS) production [49]. The mechanisms of action of the KD also include optimizing mitochondrial metabolism and neurotransmitter function, strengthening neural network stability, and improving oxidative stress and inflammation.…”
Section: Etiopathogenesis and Potential Role Of The Ketogenic Dietmentioning
confidence: 99%
“…In a mouse model highly susceptible to seizures (DBA/2J), ketogenic diet consumption was able to successfully target sensory gating deficits (Tregellas et al, 2015), a consistently reported neurocognitive phenotype for schizophrenia spectrum populations (Earls et al, 2016). In addition, Kraeuter et al (2015) demonstrated that the administration of a ketogenic diet to NMDA receptor hypofunction mouse model of schizophrenia (MK-801) normalized model induced behaviors, led to weight loss, decreased glucose levels, and elevated β-hydroxybutyrate.…”
Section: Schizophrenia Empirically Based Diets and Nutritional Suppmentioning
confidence: 99%